2008
DOI: 10.1097/ta.0b013e318047e005
|View full text |Cite
|
Sign up to set email alerts
|

Major Depression and Posttraumatic Stress Disorder Symptoms Following Severe Burn Injury in Relation to Lifetime Psychiatric Morbidity

Abstract: Two-thirds of burn survivors exhibit a history of lifetime psychiatric disorders. Those with a psychiatric history have a higher risk of postburn psychiatric problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
76
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(77 citation statements)
references
References 38 publications
0
76
0
1
Order By: Relevance
“…In this regard, staying in a positive mood and avoiding perceptions of distress and negative feelings, may be also one of the great challenges when trying to overcome post-traumatic stress symptoms 14,25,31,32,34 . In contrast, having a previous psychiatric disorder 31,33 or developing an additional comorbid mental health problem during the acute care period 12,24,29,33 , are both vulnerability factors for PTSD development.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, staying in a positive mood and avoiding perceptions of distress and negative feelings, may be also one of the great challenges when trying to overcome post-traumatic stress symptoms 14,25,31,32,34 . In contrast, having a previous psychiatric disorder 31,33 or developing an additional comorbid mental health problem during the acute care period 12,24,29,33 , are both vulnerability factors for PTSD development.…”
Section: Discussionmentioning
confidence: 99%
“…Many burns patients also go on to experience clinically significant depressive symptoms with post-discharge rates ranging from 13% -54% [2] and rates at 12 months post-burn varying from 13% to 34% [5].Yet, not all burns survivors experience persistent depressive symptoms. By identifying factors which influence the development and course of depression, it may be possible to determine which burns patients are at greater risk of developing psychological problems in the early stages of rehabilitation so that psychological treatment models can focus on those with the greatest need [6].…”
Section: Introductionmentioning
confidence: 99%
“…It was also verified that most patients had severe depression before the injury, while only two participants did not experience any previous episode of psychiatric disorder (57) . In this review, studies showed that depression was more present in patients after the burn and that greater TBSA burned and hand and face burn visibility can increase the chance of developing depression, besides being related with limitations in social and occupational activities (34) .…”
Section: Discussionmentioning
confidence: 93%
“…As identified in a recent study (57) , not included in this review, the pre-burn mental health condition can interfere in the rehabilitation process, as it can lead to worse psychosocial adjustment and can also influence improvements in physical functions.…”
Section: Discussionmentioning
confidence: 99%